REVITALISASI KEARIFAN LOKAL SEBAGAI STRATEGI AKTUALISASI NILAI-NILAI PANCASILA DALAM KERANGKA KONSTITUSIONAL UNDANG-UNDANG DASAR - Fajariyadi Aris Dwianto; Zainudin Hasan (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The modern era, characterized by globalization and digitalization, presents significant challenges to the preservation of Indonesia’s local wisdom values. The moral and social values that once served as the foundation of community life are gradually experiencing degradation and a loss of relevance. Local wisdom plays an essential role as a source of noble values that align with the principles of Pancasila as the nation’s ideological foundation and the 1945 Constitution (UUD 1945) as the constitutional basis of national governance. This study aims to analyze strategies for revitalizing local wisdom as a form of actualizing the values of Pancasila within the constitutional framework of the 1945 Constitution in the modern era. The research employs a descriptive qualitative method using a literature study approach. The findings indicate that the revitalization of local wisdom contributes to strengthening national character, fostering social ethics, and enhancing constitutional awareness among citizens. The integration of local cultural values with the principles of Pancasila and the 1945 Constitution serves as an effective strategy to preserve national identity and reinforce moral and ideological resilience amid the dynamics of globalization.